MODEL KONTEN DIGITAL UNTUK MENINGKATKAN MINAT INVESTASI MASYARAKAT AWAM PADA TRADING BERJANGKA - Mahatvani, Evelina Dewi; Supriyono, Supriyono (STKIP Pesisir Selatan, 2025)
The rise of digital platforms has significantly influenced public interest in various forms of investment, particularly futures trading. Many beginners find the terminology and mechanisms of futures trading complex and intimidating, which discourages them from participating. Digital content that is engaging, interactive, and easy to understand can effectively increase awareness and interest among novice investors. Visual elements, step-by-step tutorials, storytelling, and interactive simulations provide practical learning experiences without real financial risk. This approach not only enhances comprehension but also boosts confidence, enabling individuals to take initial investment steps more readily. The integration of educational and entertaining content, combined with interactive engagement, has proven to be a key factor in motivating public participation in futures trading. Moreover, social media platforms play a vital role in disseminating educational investment content to a wide audience. Consistent and well-structured content that includes real-life examples, risk management strategies, and practical applications helps novice investors perceive the benefits and feasibility of futures trading. The use of simple language, relatable analogies, and interactive elements strengthens understanding and builds trust in digital content. As a result, audiences become more motivated and prepared to engage in investment activities.